G453(P) 'Between the flags' paediatric early warning system is a sensitive tool to detect deterioration in children from district general hospitals admitted to paediatric intensive care. (24th May 2017) - Blackstone, B; Sharmila, A; Pienaar, A; Bevan, R; Cheung, R
Abstract : Aims: Up to 3% of hospitalised paediatric patients are at risk of sudden deterioration. Paediatric early warning systems (PEWS) aim to identify at-risk patients to assist clinical decision-making. Although many UK hospitals use PEWS, there is no national standard. Our hospital introduced a new PEWS in August 2015, based on the Australian 'Between the Flags' system. Each physiological parameter is graphed in colour coded bands (red – severely deranged; amber – very deranged; blue – moderately deranged; white – normal), with no numerical scoring. In Australia, 'Between the Flags' decreased the proportion of deteriorating patients who were not appropriately escalated and admitted to paediatric intensive care (PICU) 1 – an improvement we have also seen in our hospital, after applying a PEWS within inpatient areas. We undertook a study to assess the suitability of this PEWS to recognising deterioration in children who were referred from regional hospitals to our PICU. Method: We retrospectively analysed referral records from our intensive care transport service to assess the sensitivity of PEWS. We hypothesised that PEWS would be sensitive enough to detect deterioration in regional hospitals, as defined by the need for PICU admission, using a threshold of one red event or three or more amber events. Clinical observations at the time of transfer request were recorded according to age-specific charts. Transfer requests from other PICUs, step-down units, and emergency departments were excluded. Results: 100 patient records fulfilling inclusion criteria were randomly selected from January and July 2016. 146 red triggers were identified. Our PEWS would have been activated in 97 out of 100 patients who were subsequently admitted to PICU – 97% sensitivity, based on a threshold of one red event or three or more amber events. With threshold of only one red event, our PEWS is 91% sensitive. Conclusion: Our PEWS is sensitive as a trigger tool for regional referring hospitals. Further study on specificity is required to identify its wider utility. Reference: Akre, M. et al . 'Sensitivity Of The Paediatric Early Warning Score To Identify Patient Deterioration'. PAEDIATRICSPEDIATRICS 125.4 (2010): e763–e769.